Structural Change in Production Networks and Economic Growth - Gaggl, Paul; Gorry, Aspen; vom Lehn, Christian (Review of Economic Studies, 2026)
We study structural change in production networks for intermediate inputs (inputoutput network) and new capital (investment network). For each network, we document that the share of output produced by services (relative to goods) is rising over time. While the relative prices of services that produce intermediates and consumption are rising, we find that the relative price of services that produce investment is falling over time. We then develop a multi-sector growth model to study these trends and their implications for economic growth. To match the relative price trends, inputs to intermediates production are complements and inputs to investment production are substitutes. Hence, structural change endogenously reallocates resources to the slowest growing intermediates producers and the fastest growing investment producers. Growth accounting exercises reveal that investment-specific technical change accounts for an increasing share of U.S. aggregate growth, with 20% of aggregate growth since 2000 due to investment structural change. Growth projections from our model show that structural change within investment networks alone can offset stagnating or declining growth in other sectors due to Baumol’s cost disease.